2002
DOI: 10.1253/circj.66.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pimobendan on Adverse Cardiac Events and Physical Activities in Patients With Mild to Moderate Chronic Heart Failure

Abstract: The long-term beneficial effects of pimobendan in the treatment of chronic heart failure (CHF) have not been established, so the present trial compared pimobendan (1.25 or 2.5mg twice daily) vs placebo in 306 patients with stable New York Heart Association class IIm or III CHF, and a radionuclide or echocardiographic left ventricular ejection fraction (LVEF) < or =45% despite optimal treatment with conventional therapy, for up to 52 weeks in a double-blind protocol. At the end of the 52 weeks of treatment, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 47 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…However, in a long-term study, early clinical trial data demonstrated a trend towards increased mortality in patients with chronic moderate heart failure treated with pimobendan [15]. Nevertheless, a recent study found a reduction in the incidence of adverse cardiac events, including worsening of heart failure and decreased functional capacity, without a significant effect on mortality in patients with mild to moderate congestive heart failure [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a long-term study, early clinical trial data demonstrated a trend towards increased mortality in patients with chronic moderate heart failure treated with pimobendan [15]. Nevertheless, a recent study found a reduction in the incidence of adverse cardiac events, including worsening of heart failure and decreased functional capacity, without a significant effect on mortality in patients with mild to moderate congestive heart failure [22].…”
mentioning
confidence: 99%
“…In human medicine, pimobendan has been reported to be safe and beneficial in patients with congestive heart failure [12,22]. However, in a long-term study, early clinical trial data demonstrated a trend towards increased mortality in patients with chronic moderate heart failure treated with pimobendan [15].…”
mentioning
confidence: 99%
“…However, the 2-year incidence in Japan will be probably lower than the data shown above based on previous clinical experience. The combined incidence of death and hospitalization for HF in Japanese patients who were treated with standard therapy was reported to be 15% for 1 year (30% for 2 years) in EPOCH 11 and 5% for 6 months (20% for 2-years) in ARCH-J. 12 Therefore, the 2-year incidence was assumed to be 25% for furosemide and the hazard ratio was conservatively set at 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Pimobendan has vasodilating properties mediated by an activation of the Ca 2+ -dependent K + -channels [11]. The oral intake of pimobendan, however, seems to improve morbidity and the physical exercise capacity of heart failure patients, as recently shown in the PICO-(Pimobendan in Congestive Failure)-trial and the EPOCH-study (Effects of Pimobendan on Chronic Heart Failure [13]). However, mortality rate was not reduced.…”
Section: Pharmacokinetics and Classification Of Ca 2+ Sensitisersmentioning
confidence: 95%